Beware of the blues: Wellbeing of coaches and support staff throughout the Olympic Games - DeWolfe, C. E. J.; Dithurbide, L. (International Journal of Sports Science & Coaching, 2022)
Being involved in major sporting events, such as the Olympic Games, is a known stressor. A growing body of evidence has found the post-Olympic period to be a particularly difficult time for athletes, leading to depression-like symptoms. The impact of major sporting events on coaches` and support staffs` wellbeing is relatively unknown. The purpose of this study was to examine the experience of wellbeing for coaches and support staff post-Olympic Games. This included pre-Olympic Games and during-Olympic Games experiences that may contribute to post-Olympic challenges. Eight coaches and support staff who attended the Olympic Games completed semi-structured interviews and visual timelines to describe their wellbeing throughout the Olympic Games. Using interpretative phenomenological analysis, themes and timelines were generated that reflect the participants` wellbeing experience. Participants described the Olympic experience as a "rollercoaster ride" of emotions, including feelings of excitement, exhaustion and low mood. The post-Olympic period was a time of particular difficulty. Suggestions to improve the wellbeing for individuals who attend the Olympic Games were identified.